(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2024)
This research aims to identify the prevalence of psychological stress among a sample of Students in Third Year of General Secondary Schools. They numbered (237) male and female students, the measure of psychological stress among students and the measure of sources of psychological stress among students of the secondary certificate examination were used to answer the research questions and hypotheses. A number of results were reached, most notably: The level of psychological stress among the research sample was high; while it is the most common source of psychological stress among research sample. While the most sources of psychological stress among students are the sources related to the exam, in addition to parental methods in dealing with secondary school students. It was also found that there were no differences between the members of the research sample on the psychological stress scale according to the gender variable, While the differences were indicative of the same scale according to the variable of the educational level of the parents and the academic specialization, and the differences were in favor of the students with Education level /Postgraduate/ of parents, and the students with scientific specialization.